2010
DOI: 10.1159/000314645
|View full text |Cite
|
Sign up to set email alerts
|

Is the JAK2 V617F Mutation a Hallmark for Different Forms of Thrombosis?

Abstract: Background/Aims: The association between venous thrombosis outside the splanchnic area as well arterial thromboembolism and the JAK2 V617F mutation, an important marker for chronic myeloproliferative neoplasms (MPN), is not completely clear. Methods: Four hundred forty-four patients with venous thrombosis of the lower/upper limbs and/or pulmonary embolism and 60 patients with ischemic stroke were screened for the JAK2 V617F mutation, factor V Leiden, and factor II G20210A. Results: The JAK2 V617F mutation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Several other studies have assessed the prevalence of the JAK2V617F mutation in patients with ischemic stroke 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ( Table 5 ), yet they differ from our study in 3 important ways. First, most previous studies only included patients with ischemic stroke who were referred for thrombophilia testing.…”
Section: Discussionmentioning
confidence: 61%
“…Several other studies have assessed the prevalence of the JAK2V617F mutation in patients with ischemic stroke 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ( Table 5 ), yet they differ from our study in 3 important ways. First, most previous studies only included patients with ischemic stroke who were referred for thrombophilia testing.…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, Zerjavic et al asserted having found a significant association between ischemic stroke and JAK2 V617F mutation in patients without MPNs. 47 Arterial thrombosis including CVEs was diagnosed in 20 (11%) of our patients with MPN. Recently, 3 large meta-analyses showed evidence for increased risk of arterial thrombosis in patients with JAK2 V617F -positive ET (OR, 1.68-2.09).…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, one patient presented with a fulminant cerebral venous sinus thrombosis, resulting in cerebral ischaemia with hemorrhagic transformation. This case indicates – besides the enhanced arterial thrombotic risk – the predisposition for venous thrombosis (including Budd–Chiari syndrome, portal/mesenteric venous thrombosis and pulmonary embolism) that MPN patients harbor .…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, assessment of inflammation markers, iron stores, mean corpuscular volume, lactate dehydrogenase and differential blood tests should follow. Although JAK2 gene mutation screening should not be routinely performed in stroke patients when a manifest or latent MPN is not suspected , upon MPN suspicion, screening for JAK2 V617F mutation is mandatory . If JAK2 V617F mutation screening remains negative, screening for further specific molecular markers (e.g.…”
Section: Discussionmentioning
confidence: 99%